Los estudios de usuarios en los planes de estudio de Biblioteconomía y documentación - Lascurain-sánchez, María Luisa (Revista General de Información y Documentación, 2008)
User studies, acknowledged as an effective tool for acquiring an understanding of user characteristics in organizations’ information an evaluation processes, have evolved considerably in both theory and methodology. Their use is uneven in the professional, research and academic domains, however, and the subject is included in very few Spanish university curricula. The present article addresses some of the education objectives of the discipline and proposes the basic subject matter to achieve them, against the backdrop of the specific competencies associated with this diploma in the White Paper on the adaptation of Library and Information Science studies to European Higher Education Area criteria.